“Doing well”: Intraoperative entrustable professional activity assessments provided limited technical feedback - Riley Brian; Natalie Rodriguez; Connie J. Zhou; Megan Casey; Rosa V. Mora; Katherine Miclau; Vivian Kwok; Liane S. Feldman; Adnan Alseidi (Surgery Open Science, 2024)
Background: Entrustable Professional Activities (EPAs) allow for the assessment of specific, observable, essential tasks in medical education. Since being developed in non-surgical fields, EPA assessments have been implemented in surgery to explore intraoperative entrustment. However, assessment burden is a significant problem for faculty, and it is unknown whether EPA assessments enable formative technical feedback. EPAs' formative utility could inform how surgical programs facilitate technical feedback for trainees. We aimed to assess the extent to which narrative comments provided through the Fellowship Council (FC) EPA assessments contained technical feedback. Methods: The FC previously collected EPA assessments for subspecialty surgical fellows from September 2020 to October 2022. Two raters reviewed assessments' narrative comments for inclusion of each skill area that makes up part of the Objective Structured Assessment of Technical Skills (OSATS). A third rater reconciled discrepant ratings. Results: During the study period, there were 3302 completed EPA assessments, including 1191 fellow self-assessments, 1124 faculty assessments, and 987 assessments without an identified assessor role. We found that assessments' narrative comments related to a median of two of the seven OSATS areas (IQR:1–2). There were no comments relevant to any of the seven OSATS areas in 16.0 % of all assessments. Conclusions: In this review of narrative comments for EPA assessments from the FC, we found that limited technical feedback of the kind included in the OSATS was provided in many assessments. These results suggest benefit to adjusting the EPA form, enhancing faculty development, or continuing additional types of targeted technical assessment intraoperatively. Key message: This analysis of narrative comments from fellowship EPA assessments showed that many assessments included limited technical feedback. To allow for continued technical feedback for fellows, these results highlight the need for further refinements of the EPA assessment form, additional faculty development, or ongoing use of other types of technical assessment.